Infrastructure Deployment in Vehicular Communication Networks Using a Parallel Multiobjective Evolutionary Algorithm. - Massobrio, Renzo; Toutouh-el-Alamin, Jamal; Nesmachnow, Sergio; Alba-Torres, Enrique (Wiley, 2017)
This article describes the application of a multiobjective evolutionary algorithm for locating roadside infrastructure for vehicular communication networks over realistic urban areas. A multiobjective formulation of the problem is introduced, considering quality-of-service and cost objectives. The experimental analysis is performed over a real map of Málaga, using real traffic information and antennas, and scenarios that model different combinations of traffic patterns and applications (text/audio/video) in the communications. The proposed multiobjective evolutionary algorithm computes accurate trade-off solutions, significantly improving over state-of-the-art algorithms previously applied to the problem.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/14768
Keywords: Sistemas inteligentes de transporte; Computación evolutiva; Optimization; Vehicular ad hoc networks; Metaheuristics